2018
DOI: 10.1186/s12943-018-0917-7
|View full text |Cite
|
Sign up to set email alerts
|

CircFAT1 sponges miR-375 to promote the expression of Yes-associated protein 1 in osteosarcoma cells

Abstract: BackgroundThere is an urgent need to identify new molecular targets for treatment of osteosarcoma. Circular RNAs are a class of endogenous RNAs that are extensively found in mammalian cells and exert critical functions in the regulation of gene expression, but in osteosarcoma the underlying molecular mechanism of circular RNAs remain poorly understood. Here we assessed the tumorigenesis properties of a circular RNA, circFAT1 in osteosarcoma.MethodsThe effects of circFAT1/miR-375/YAP1 was evaluated on human ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 52 publications
4
98
0
Order By: Relevance
“…After YTHDF2 binds YTHDF3, which carries YAP pre-mRNA containing m 6 A, YTHDF2 presents YAP mRNA to AGO2, and then AGO2 recruits other molecules to form RISC system to facilitate YAP mRNA decay, reducing YAP protein level. It has been recently shown that microRNAs, such as miR-195, miR-375, and others, decrease YAP mRNA levels by binding to YAP 3′UTR [37,38]. Conversely, on the mRNA translation level, recognition and binding of m 6 A by YTHDF1 and YTHDF3 result in enhanced protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…After YTHDF2 binds YTHDF3, which carries YAP pre-mRNA containing m 6 A, YTHDF2 presents YAP mRNA to AGO2, and then AGO2 recruits other molecules to form RISC system to facilitate YAP mRNA decay, reducing YAP protein level. It has been recently shown that microRNAs, such as miR-195, miR-375, and others, decrease YAP mRNA levels by binding to YAP 3′UTR [37,38]. Conversely, on the mRNA translation level, recognition and binding of m 6 A by YTHDF1 and YTHDF3 result in enhanced protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…For YAP, the only upstream regulatory transcription factor reported so far is cyclic adenosine monophosphate response element-binding protein (CREB) [46]. In cancer, both YAP and TAZ RNA are frequently increased, but the mechanisms behind this upregulation remain largely elusive and may involve both transcriptional and post-transcriptional mechanisms through suppression of the YAP/TAZ regulatory microRNAs, including miR-15a, miR-141-3p, mir-194, miR-195, miR-375, miR-381, miR-584, miR-125, miR-185, miR-9-3p and miR-129-5p, to name a few [47][48][49][50][51][52][53][54][55][56][57].…”
Section: Transcriptional and Post-transcriptional Regulators Of Yap Amentioning
confidence: 99%
“…MicroRNAs miR-214-3p and miR-23a-5p shed from osteoclasts in exosomes downregulate osteoblast function by targeting upstream YAP regulatory fibroblast growth factor receptor and the YAP/RUNX2 transcriptional complex, respectively [82][83][84]. A circular RNA expressed from the second exon of the FAT Atypical Cadherin 1 gene (circFAT1) was demonstrated to sponge the YAP suppressive microRNA miR-375, thus upregulating YAP1 in osteosarcoma [52]. Vice versa, nuclear YAP/TAZ have also been reported to regulate microRNA biogenesis.…”
Section: Role Of Micrornas In Yap/taz-regulated Circuitriesmentioning
confidence: 99%
“…The gap between the predicted and functional observed effects of miR-375 knockdown are not entirely unexpected. Several reports provide a possible explanation: long non-coding RNAs, such as TINCR, HNGA1 and CircFAT1 act as a miR-375 sponge [27][28][29]. Thus, the highly expressed miR-375 may be not functionally active in MCC cells.…”
Section: Discussionmentioning
confidence: 99%